FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA ORGANISASI SEKTOR PUBLIK (STUDI EMPIRIS PADA DINAS-DINAS DI KOTA JAMBI) - Muhammad Ridwan; Mus'id Mus'id (Jurnal Riset Akuntansi Terpadu, 2019)
This present study is intended to identify the factors contributing to the organizational performance of the public sector, that is, the departements of Jambi city. The quantitative approach is used. The population of this study is the Head of Financial Section and the financial department staffs in the Office of the city of Jambi. The sampling method used is saturated sample. The amount of questionnaires distributed is 75 and that can be used is 55 questionnaires. Statistical method used is multiple linear regression analysis. Data analysis tools used is IBM SPSS version 22.0 program. The result of analysis showed that (1) the clear and measurable objective significantly affected the organiational performance of the departements of jambi city; (2) the working motivation significantly contributed to the organizational performance of the departements of jambi city; (3) the performance measurement system significantly contributed to the organizational performance of the departements of jambi city; (4)  the incentive does not affect the organizational performance of the departements of jambi city; (5) decentralization significantly affected the organizational performance of the departements of jambi city; (6) budgetary participation significantly contributed to the organizational performance of the departements of jambi city; (7) the variables of clear and measurable objective, working motivation, performance measurement, incentive, decentralization, budgetary participation significantly affected the organizational performance of the departements of jambi city.